Pengaruh Metode Eksperimen Terhadap Perkembangan Keterampilan Proses Sains Anak - Khalida Ayuni; Putri Rahmi (Jurnal Kajian Anak)
Teachers should make learning more active and not boring, so that children are able to develop their knowledge and skills through activities and learning provided by teachers both in the classroom and outside the classroom using various methods such as experimental methods. The aim of this research is to determine the effect of experimental methods on the development of science process skills in children at RA Fathun Qarib. The research method used is a quantitative approach, and a pre-Experimental Design (Non-Design) design using a One-Group Pretest-Posttest Design type. Data collection techniques use observation and documentation. The subjects of this research were 25 children in class B3 RA Fathun Qarib. The data analysis technique in this research uses the Normality Test and t-test with a significance level of 5%. The results of the research can be concluded that the Experimental Method influences the development of children's science process skills at RA Fathun Qarib.